2021
DOI: 10.1038/s41467-021-25229-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct deoxygenative borylation of carboxylic acids

Abstract: Carboxylic acids are readily available, structurally diverse and shelf-stable; therefore, converting them to the isoelectronic boronic acids, which play pivotal roles in different settings, would be highly enabling. In contrast to the well-recognised decarboxylative borylation, the chemical space of carboxylic-to-boronic acid transformation via deoxygenation remains underexplored due to the thermodynamic and kinetic inertness of carboxylic C-O bonds. Herein, we report a deoxygenative borylation reaction of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Control experiments showed that a photocatalyst, cobalt, acid, light, and an inert atmosphere were all vital for this photoinduced oxidative cross-coupling reaction. Other boron reagents were ineffective, which might be attributed to their prohibitive oxidation potentials ( E red > +2.5 V vs SCE for cyclohexylboronic acid, Cy-B­(OH) 2 , and its pinacol ester, Cy-Bpin). , Notably, among some commercial photocatalysts evaluated, [Ru­(bpy) 3 ]­(PF 6 ) 2 , eosin Y, rose bengal, and rhodamine 6G brought poor results of the Minisci alkylation (<25%), while Nicewicz’s catalyst (Mes-Acr-Ph + ) gave a slightly lower yield (87%).…”
Section: Resultsmentioning
confidence: 99%
“…Control experiments showed that a photocatalyst, cobalt, acid, light, and an inert atmosphere were all vital for this photoinduced oxidative cross-coupling reaction. Other boron reagents were ineffective, which might be attributed to their prohibitive oxidation potentials ( E red > +2.5 V vs SCE for cyclohexylboronic acid, Cy-B­(OH) 2 , and its pinacol ester, Cy-Bpin). , Notably, among some commercial photocatalysts evaluated, [Ru­(bpy) 3 ]­(PF 6 ) 2 , eosin Y, rose bengal, and rhodamine 6G brought poor results of the Minisci alkylation (<25%), while Nicewicz’s catalyst (Mes-Acr-Ph + ) gave a slightly lower yield (87%).…”
Section: Resultsmentioning
confidence: 99%
“…This protocol could apply to the coupling between the other fifteen different potassium benzyltrifluoroborates ( Li et al., 2012 , 2020 , 2021a ; Wang et al., 2018 ) and sixteen aryl halides. For details of the scope of this metallaphotoredox Suzuki-Miyaura coupling, please refer to Li et al.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Capitalizing on these simplified conditions, a site-selective SM cross-coupling between 37 and 38 was accomplished, affording the mono-debrominated product (39) as the paracyclophane precursor. 86,87 Ni-catalyzed metallaphotoredox cross-couplings Encouraged by the successful application of Ni 2+ /PPQN 2,4-di-OMe in SM cross-couplings, other redox-neutral C-C bond-forming reactions were attempted with the same Ni-based transformative platform (Figure 3). In place of RBF 3 K, Hantzsch's ester (40), which could be easily derived from the corresponding aldehydes, was also shown as an efficacious radical source for our Ni-catalyzed metallaphotoredox C(sp 3 )-C(sp 2 ) cross-coupling (Figure 3; Equation 1).…”
Section: Articlementioning
confidence: 99%